A review of Proterozoic to Early Paleozoic lithotectonic terranes in the northeastern Appalachian orogen of New Brunswick, Canada, and their tectonic evolution during Penobscot, Taconic, Salinic, and Acadian orogenesis - Fyffe, Leslie; Johnson, Susan; van Staal, Cees (Atlantic Geology, 2011)
ABSTRACT Geological relationships preserved in the New Brunswick segment of the Appalachian orogen are key to deciphering the complex tectonic events that occurred during the closing of the Paleozoic Iapetus Ocean. These events can be explained in terms of geodynamic interactions between eight lithotectonic terranes. The first, the Caledonia terrane, comprises Neoproterozoic volcanic arc sequences and comagmatic plutons considered to form part of the microcontinent of Avalonia. The seven other terranes are associated with the microcontinent of Ganderia and consist of (1) Brookville terrane–Mesoproterozoic to Neoproterozoic platformal carbonates and Neoproterozoic to Early Cambrian plutonic rocks, (2) New River terrane–Neoproterozoic volcanic arc sequences and comagmatic plutons overlain by a Cambrian Penobscot volcanic arc sequence, (3) Annidale terrane–Upper Cambrian to lower Lower Ordovician Penobscot volcanic arc-backarc sequence and unconformably overlying upper Lower Ordovician volcanic sequence, (4) St. Croix terrane–Cambrian to Upper Ordovician sedimentary sequence deposited on the passive margin of the New River terrane, (5) Miramichi terrane–Cambrian to Lower Ordovician sedimentary sequence and unconform-ably overlying Middle to Upper Ordovician Tetagouche volcanic backarc sequence; and Lower to Middle Ordovician Meductic volcanic arc sequence, (6) Elmtree terrane–Middle to Upper Ordovician backarc ophiolitic sequence, and (7) Popelogan terrane–Middle to Upper Ordovician volcanic arc sequence. In New Brunswick, closure of the Iapetus Ocean is attributed to four major tectonic episodes: (1) the Penobscot orogeny, which accreted the Miramichi, Annidale, and St. Croix terranes to the New River terrane on the trailing edge of Ganderia by closing a Penobscot backarc basin in the Early Ordovician, (2) the Taconic orogeny, which accreted the Popelogan terrane on the leading edge of Ganderia to the Laurentian margin in the Late Ordovician and effectively closed the main tract of the Iapetus Ocean, (3) the Salinic orogeny, which accreted the Elmtree and Miramichi terranes to the Laurentian margin by closing the Tetagouche backarc basin in the Silurian, and (4) the Acadian orogeny, which accreted the Caledonia terrane (Avalonia) to the Brookville and New River terranes on the trailing edge of Ganderia in the latest Silurian to earliest Devonian and in the process closed the last remaining oceanic tract in the northeastern Appalachians.